Audience Gratification through Social Media-Based Da'wah: Communication Strategies of Young Da'i in Bengkulu - Mukhlizar; Zakiyuddin Baidhawy; Samsul Hidayat (DAWUH : Islamic Communication Journal, 2026)
The rise of the digital era has significantly transformed the practice of Islamic da'wah, creating new opportunities for religious communication through social media. Platforms such as TikTok, Instagram, and YouTube have become strategic channels for disseminating Islamic messages, particularly among younger audiences who are deeply engaged in digital environments. This development requires young da'i to adopt communication strategies that are relevant to the preferences, expectations, and media habits of online users. This study aims to examine the digital communication strategies employed by young da'i in Bengkulu City and to analyze how these strategies address audience needs through the perspective of Uses and Gratifications Theory (UGT). The research uses a qualitative approach. Data were collected through in-depth interviews, digital observation, and documentation of da'wah content produced by five active young da'i across various social media platforms. The findings identify three main communication strategies. First, young da’i tailor their messages according to audience segmentation. Second, they use creative and visually engaging content formats to attract audience attention and increase message appeal. Third, they build participatory communication through comments, responses and audience feedback. These strategies reflect the four main dimensions of UGT, namely information, personal identity, social integration, and entertainment. This study contributes to the growing scholarship on digital da'wah communication and offers practical recommendations for strengthening social media-based da'wah training and enhancing digital literacy programs.